Valor da Complacência Atrial Esquerda após Valvoplastia Mitral Percutânea na predição de desfechos clínicos - Guilherme Rafael Sant'Anna Athayde (2021)
Introduction: Left atrial compliance (Ca) is one of the most important determinants of the pulmonary hypertension in patients with severe rheumatic mitral stenosis. Percutaneous mitral valvulopasty (PMV) leads to increased Ca as a consequence of opening the valve. However, the prognostic value of Ca after PMV is not yet defined. Aim: To verify if Ca invasively measured immediately after PMV can predict adverse cardiovascular events at a long-term follow- up. Methods: A total of 341 patients who were referred for PMV in a tertiary center were initially considered for enrollment. After the procedure, 27 patients (7.9%) were excluded due to severe mitral regurgitation, 1 patient (0.3%) was excluded due to cardiac tamponade and 1 patient (0.3%) was excluded due to pregnancy. Three hundred and twelve patients underwent echocardiogram and right and left heart catheterizations with pressure recordings before and after PMV. Brain natriuretic peptide (BNP) levels measurements were also obtained. Ca was calculated prior and post PMV with the following formula: Stroke volume (SV)/ left atrial pressure variation during ventricular systole (mL/ mmHg). The SV was obtained by dividing the cardiac output (CO), calculated by the Fick method, by heart rate. The left atrial pressure variation was obtained by subtracting the nadir of the X descent from the peak of the V wave. The adverse cardiovascular events were defined as cardiovascular death or the need for surgical mitral replacement. Results: The mean age of the patients was 45 ± 12 years. Two hundred and sixty four (85%) were female. There were 58 events (12 cardiovascular deaths and 46 mitral valve replacement) during the median follow-up of 3.2 years (range from 1 month to 8 years). The incidence of cardiovascular events was 5.97 events/ 100 patient-years and the mortality rate was 1.24 deaths/ 100 patient years. The patients who experienced an event were older, more symptomatic, used more diuretics and had more atrial fibrillation (AF) and systemic hypertension. The immediate success of the PMV was an important predictor of event-free survival. The echocardiographic data such as mitral valve area (MVA) and transmitral gradient were more favorable in the group without event. Finally, the hemodynamic data pre PMV did not differ significantly. However, after the procedure the group without the event had higher cardiac index, lower left atrial (LA) pressure and higher Ca. There were no differences between the groups in pulmonary artery pressure levels either measured non-invasively or invasively. BNP levels were significantly lower in the group without events. In the final multivariate model, the independent predictors were age (hazard ratio [HR] 1.042 Confidence Interval [CI] 95% 1.01- 1.07) and post PMV variables including MVA (HR 0.81; CI 95% 0.61- 0.93), the degree of tricuspid regurgitation (TR) (HR 2.87 CI 95% 1.24- 6.62), the change in BNP levels (HR 0.57 CI 95% 0.40- 0.81) and Ca (HR 0.86 CI 95% 0.75- 0.98). The inclusion of Ca in the prognostic model resulted in a better performance in predicting adverse cardiovascular events with a C- statistics of 0.820. Conclusion: Left atrial compliance post PMV has prognostic value independent of MVA, TR severity, or change in BNP levels. Theses results indicate that Ca may be a success marker of the procedure with impact on free event survival at a long-term follow- up.